2014
DOI: 10.11604/pamj.2014.19.279.4784
|View full text |Cite
|
Sign up to set email alerts
|

Para testicular rhabdomyosarcoma in adults: three case reports and review of literature

Abstract: Paratesticular embryonal rhabdomyosarcoma (RMS) is a rare tumor arising from the mesenchymal tissues of the spermatic cord, epididymis, testis and testicular tunics. We report three cases of adult paratesticular RMS, two embryonic and one pleomorphic rhabdomyosarcoma. All the patients underwent diagnostic orchidectomy. The work up investigations revealed lung metastases. Chemotherapy with Ifosfamide and Doxorubicin was used in two cases, whereas Vincristin- Actinomycin D and Cyclophosphamide was received in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…[3,4] Spalteholz et al reported that 80% of RMS occurs in children below 12 years, whereas Boudahna et al observed that RMS has two peaks one at the age of 4 years and the second at 18 years. [1,5] Lee et al also reported that 80% of cases occur before 21 years of age and the rest 20% occur in adults. [6] RMS is more common in boys with a ratio of 3:1.…”
Section: Review Of Literaturementioning
confidence: 99%
“…[3,4] Spalteholz et al reported that 80% of RMS occurs in children below 12 years, whereas Boudahna et al observed that RMS has two peaks one at the age of 4 years and the second at 18 years. [1,5] Lee et al also reported that 80% of cases occur before 21 years of age and the rest 20% occur in adults. [6] RMS is more common in boys with a ratio of 3:1.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Az diferansiye leiomyosarkomu morfolojik olarak tanımak zorken, düz kas yönüne diferansiasyonunu immünohistokimyasal yöntemlerle göstermek (kasa spesifik aktin, DKA ve desmin pozitifliği) yardımcı olabilir. Rabdomyosarkom, paratestiküler bölgede çocuklarda en sık gözüken sarkom olup yaklaşık %80'i 21 yaşından önce görülür (23). Paratestiküler bölgede geliştiğinde spermatik kord veya epididimle ilişkili, makroskopik olarak lobüle, parlak, iyi sınırlı bir kitle olarak izlenir.…”
Section: Sarkomlarunclassified
“…Paratestiküler bölgede geliştiğinde spermatik kord veya epididimle ilişkili, makroskopik olarak lobüle, parlak, iyi sınırlı bir kitle olarak izlenir. Ancak mikroskopik olarak çevreye infiltre olduğu görülür (23,24). Hastalar hızla büyüyen, ağrısız kitle şikayetiyle kliniğe başvururlar.…”
Section: Sarkomlarunclassified
See 2 more Smart Citations